AC and DC fault ride through hybrid MMC integrating wind power. Issue 13 (4th December 2017) - Cao, Shuai; Xiang, Wang; Yao, Liangzhong; Yang, Bo; Wen, Jinyu
Abstract : To transmit bulk wind power over long distance, using high‐voltage direct current (HVDC) transmission technology with overhead lines is a preferred approach. Since direct current (DC) faults are frequent in overhead lines, this study adopts the hybrid modular multilevel converter (MMC) based on half bridge sub‐module and full bridge sub‐module to integrate wind power. The design of controllers, the alternating current (AC) and DC fault ride‐through strategy of the hybrid MMC‐HVDC system will be presented. Since the wind power continues injecting into the system during the faults, the damping resistor is adopted to dissipate the surplus wind power. The coordination control of the damping resistor and the chopper resistor inside the wind turbine is designed. Finally, the performance during AC, DC faults ride though is verified by extensive simulations.